Das Prämonstratenserkloster Belbuck als eine Keimzelle der Reformation im südlichen Ostseeraum - Ehricht, Christoph (Gdański Rocznik Ewangelicki, 2017)
The monastery in Belbuck near Treptow upon Rega in the former Duchy of Pomerania (today Białoboki / Trzebiatów in Pomorze Zachodnie/ Westpomerania, Poland) was founded in the end of the 12th century by Premonstratensians from Lund. In the beginning of the 16th century some very im-portant theologiansworked there. They were friends of Johannes Bugenhagen who, later on, becamea friend of Martin Luther and Reformer of the northern Germany and of the Kingdom of Denmark. His friends in Belbuckwere Johannes Boldewan, Johannes Äpinus, Christian Ketelhodt, Andreas Knopken. Connected with the monastery was a nunnery in Treptow, where Elisabeth von Meseritz (Elisabeth Cruciger) lived. They all exerted great influence on the Reformation and stabilization of the Lutheran Church from Copenhagenas far as Riga. The monastery itself has been, since 1616, completely destroyed, but remembrance of its history may be helpful for a more diverse understanding of very various processes occurring during the early time of “Reformation” in the Southern Baltic Sea region.
Keywords: białoboki

Archäologische Forschungen am Prämonastratenserstift Belbuck bei Treptow an der Rega - Biermann, Felix Paul; Dworaczyk, Marek; Rebkowski, Marian (Baltische Studien, 2015)
Keywords: białoboki

Belbuc, Belboch, Bialoboki. Über das Projekt zur Erforschung des Prämonstratenserstift - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Belbuc, Belboch, Bialoboki. Wprowadzenie do badan klasztoru prem onstratensów - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Klasztor premonstratensów w Białobokach: archeologia i historia - Rębkowski, Marian; Biermann, Felix (Instytut Archeologii i Etnologii Polskiej Akademii Nauk : Ośrodek Archeologii Średniowiecza Krajów Nadbałtyckich, 2015)
Das Prämonstratenserstift in Belbuck : Archäologie und Geschichte
Keywords: białoboki

Kolbacz (Kolbatz) and Bialoboki (Belbuck) - archaeology of two 12th century monasteries in Pomerania - Rębkowski, Marian (Glaube, Macht und Pracht. Geistliche Gemeinschaften des Ostseeraums im Zeitalter der Backsteingotik, 2009)
Keywords: białoboki

Wyniki analizy antropologicznej szczatków kostnych z cmentarza przyklasztornego premonstratensów (norbertanów), odkrytych w Bialobokach (gmina Trzebiatów, województwo zachodniopomorskie) - Teul, Iwona (Acta archaeologica Pomoranica, 2009)
Keywords: białoboki

Klasztor w Białobokach w świetle badań archeologicznych z lat 2003-2006 - Rębkowski, M.; Biermann, F. (Trzebiatów - spotkania pomorskie - 2006 r., 2007)
Keywords: białoboki

Das Kloster Belbuck b. Treptow - Bosse, H. (Unser Pommerland : Monatsschrift für das Kulturleben der Heimat, 1931)
Keywords: białoboki

Belbuck, Prämonstratenserkloster - Hoogeweg, H. (Die Stifter und Klöster der Provinz Pommern, 1924)
Keywords: białoboki

Belbuck. Prämonstratenserkloster. - Hoogeweg, Hermann (Die Stifter und Klöster der Provinz Pommern, 1924)
Keywords: białoboki

Kloster Belbuck um die Wende des 16. Jahrhunderts - Paap, Walter (Baltische Studien, 1912)
Keywords: białoboki

Die Ruinen des Klosters zu Belbog - Temme, Jodocus Donatus Hubertus (Die Volkssagen von Pommern und Rügen, 1840)
Keywords: białoboki

Namen der Dörfer samt allen Pertinentien des Klosters Belbog (Baltische Studien, 1839)
Keywords: białoboki

Das Kloster Belbog bey Treptow an der Rega - Brummer, G.F. (Baltische Studien, 1833)
Keywords: białoboki